The role of nitrogen-nitrogen pairs in the deviation of the GaAsN lattice parameter from Vegard’s law - Wang, S. Z. (2013)
We propose several physical mechanisms that may account for the difference between the nitrogen composition in GaAsN materials measured by secondary ion mass spectroscopy and x-ray diffraction. A simplified model proposed here proves that Vegard’s law remains valid as long as all nitrogen atoms in the GaAsN alloys are located substitutionally at the arsenic sites. The theoretical results based on N-N pair defects are in good agreement with the experimental data, suggesting that the N-N pairs are the predominant nitrogen-related defects that cause deviation from the GaAsN lattice constant predicted by Vegard’s law.